Effect and mechanism of chlortetracycline on phosphorus removal performance in EBPR system - YAN Yumeng; REN Chenzhu; WANG Shaopo; LIU Lingjie; MENG Fansheng; QIU Chunsheng; YU Jingjie (Gongye shui chuli)
A sequencing batch reactor(SBR) was used with casein hydrolysate as the sole carbon source to investigate the impact of chlortetracycline(CTC) on the enhanced biological phosphorus removal(EBPR) system. The results indicated that the removal rates of PO₄³⁻ and COD were comparable to those of the control group when the CTC concentration was 0.1 mg/L. However, the removal rate of PO₄³⁻ decreased from 90.0% to 75.0%, and the removal rate of COD decreased from 95.3% to 90.4% when the CTC concentration was increased to 1.0 mg/L. Further, at CTC concentration of 5.0 mg/L, the removal rate of PO₄³⁻ was only 40.0%, indicating significant inhibition, while the removal rate of COD still reached 85.1%. The inhibitory effect of chlortetracycline on the biological phosphorus removal system was intensified with the increase of chlortetracycline dosage. Analysis of matrix metabolism in typical cycles revealed that chlortetracycline had a more pronounced effect on aerobic phosphorus uptake in biological phosphorus removal, which would reduce glycogen and polyphosphate synthesis. Metagenomic analysis demonstrated that the presence of chlortetracycline could inhibit the metabolic pathways associated with phosphorus removal and the synthesis of key enzymes in poly-β-hydroxybutyrate(PHB) synthesis. This inhibition ultimately resulted in the deterioration of the phosphorus removal performance of the system.